2016
DOI: 10.1002/elan.201600006
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Bismuth Modified Carbon Thread Electrode for Simultaneous and Highly Sensitive Cd (II) and Pb (II) Determination

Abstract: Bismuth film modified and chemically activated carbon micro‐thread electrodes were investigated for the simultaneous determination of Cd(II) and Pb(II) using square wave anodic stripping voltammetry. The carbon thread electrode was characterised using both surface and electrochemical techniques. Electrochemical impedance spectroscopy (EIS) studies demonstrated that the H2SO4/IPA‐treated carbon thread electrode showed a much improved resistance response (Rct=23 Ω) compared to the IPA‐untreated carbon thread (Rc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 65 publications
(59 reference statements)
0
6
0
Order By: Relevance
“…This versatility allows carbon materials to be tailored for a wide range of applications. Various carbon-based materials have been explored in numerous sensing applications [ 55 , 56 , 57 , 58 , 59 , 60 , 61 ]. This adaptability is particularly relevant in the context of arsenic detection, where the specific properties of nanostructured carbon allotropes can be leveraged for enhanced sensitivity and selectivity.…”
Section: Nanomaterials and Colorimetric Advancementsmentioning
confidence: 99%
“…This versatility allows carbon materials to be tailored for a wide range of applications. Various carbon-based materials have been explored in numerous sensing applications [ 55 , 56 , 57 , 58 , 59 , 60 , 61 ]. This adaptability is particularly relevant in the context of arsenic detection, where the specific properties of nanostructured carbon allotropes can be leveraged for enhanced sensitivity and selectivity.…”
Section: Nanomaterials and Colorimetric Advancementsmentioning
confidence: 99%
“…This distinctly demonstrated that the proposed sensor can be used without any primary changes in its sensitivity for up to few days. A comparison of the Pb 2+ detection using different organic compound-based sensors [26][27][28][29][30][31][32][33] is discussed and presented in Table 3. According to the comparative study of previous sensors with various organic materials, the highest sensitivity value was found with our fabricated sensor probe (BDMMBSH/GCE/NF) for the detection of lead ions.…”
Section: Evaluation Of Sensor Efficiencymentioning
confidence: 99%
“…The interference study of the sensor; atomic ratios calculated by XPS and EDS analysis; EDS mapping results; small angle XRD patterns, XPS and high resolution spectra of materials; cyclic voltammograms of BiOCl-KIT-6/GCE; SWASV running parameters as well as recorded assay curves of Pb 2 + using different electrodes are detailed in the Supporting Information. BiBE SWASV -1.40 180 10-100 0.093 [32] Bi/Au-GN-Cys/GCE SWASV -1.20 800 0.50-40 0.05 [33] BiF-EPPGE SWASV -1.20 240 0.2-200 0.101 [34] nBi-BchCPE DPAdSV -0.80 30 1.036-207.2 0.292 [35] Bi -CTE SWASV -1.10 300 5-110 0.87 [36] BiOCl-KIT-6/GCE SWASV -1.10 120 0.2-300 0.033 This work a 10 min deposition time; N/A: Not available 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57…”
Section: Supporting Information Summarymentioning
confidence: 99%